The species and cultivars of mango in Madiun and its surroundings; the development and its problems - NURUL SUMIASRI; JITNO RIJADI; DODY PRIADI (Society for Indonesian Biodiversity, 2006)
The East Java province is one of distribution areas of mango in Indonesia. These plants can be found almost in all areas in that province. The central distribution in some regency namely Probolinggo, Pasuruan, Banyuwangi, Kediri and Tulungagung. The aim of this research was to know species diversities among diversity within species (cultivar) which was planted recently since the genetic erosion was going fast. Therefore several areas in Madiun and its surroundings (Ngawi, Nganjuk, Kediri, and Tulungagung) were selected for this study. The results as follows: there were two species mango planted in those areas namely Mangifera indica L. (14 cultivars) and Mangifera odorata Griff. (2 cultivars). According to the taste, can be classified into good (for example ‘arumanis’, ‘santog’,’madu’, ‘manalagi’, ‘golek’) and not too good taste (for example ‘kopyor’, ‘kelem’, ‘dodonilo’, ‘cempuro’). According to the diversity status,the following cultivars could be classified as endangered (i.e. pakel, madu, kopyor, santog gunung, dodonilo, cempuro and pelem lanang). Aside of those cultivars, however, we might find some cultivars which are commonly abundance (i.e. gadung, podang, podang gunung and podang sawahan). Besides that developing, marketing and processing still need to be developed to increase its added value, because in practice the marketing and processing still traditionally system. © 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: variation, species, cultivars, mango, Madiun